Synthesis of LAS/ZnO/ZnWO4 3D rod-like heterojunctions with efficient photocatalytic performance: Synergistic effects of highly active site exposure and low carrier recombination. Issue 11 (1st August 2019) - Wu, Yadong; Tie, Junyu; Chen, Cheng; Luo, Ni; Yang, Dingming; Hu, Wenyuan; Liu, Xun
Abstract: A photocatalytic nano-material containing LAS/ZnO/ZnWO4 3D rod-like heterojunctions was successfully synthesized using hydrothermal and mechanical force solid phase methods. Its phase, morphology, specific surface, and electrochemical characteristics, as well as the degraded performance under ultraviolet light of the sample pollutant RhB in its presence, were all investigated. Compared with pure ZnO, pure ZnWO4 and ZnO/ZnWO4 composites, LAS/ZnO/ZnWO4 (LZx ZW1-x ) composites have a smaller particle size, larger specific surface area, stronger photoelectric chemical properties and better photocatalytic performance. Notably, the rate of degradation of RhB by LZ0.92 ZW0.08 reaches 98.0% in 30 min, which is 100%, 500% and 25% higher than that found with pure ZnO, pure ZnWO4 and ZnO/ZnWO4, respectively. This is because the n-n heterojunction of ZnO/ZnWO4 loads well on schizolytic luffa sponge (LAS) with its large specific surface area. More active sites are exposed at the heterojunction, increasing the probability of contact between pollutants and the semiconductor composites, and vacancy defects of C atoms are present in LAS, acting as the capture center for photogenerated carriers. This facilitates the transfer of photogenerated electrons or holes at the ZnO/ZnWO4 heterojunction and reduces the rate of recombination of photogenerated carriers. Capitalizing on this idea of two-factor coupling and synergistic enhancement of photocatalyst performance can help make treatment of environmental pollution more efficient. Highlights: The synergy of LAS/ZnO/ZnWO4 's combination of heterojunctions and highly active site exposure improves removal of RhB. Porous LAS not only combats aggregation and increases the number of active sites but also improves light utilization. Highly efficient at removing organic pollutants, LAS is a promising material for environmental pollution control.